Analysing the Impact of Industrial Revolution 4.0 on Traditional Occupations and Community Adaptation Efforts in Bali - Heri Aji Setiawan (West Science Social and Humanities Studies, 2024)
This research investigates the impact of Industrial Revolution 4.0 on traditional occupations in Bali, employing a quantitative approach with Structural Equation Modeling and Partial Least Squares (SEM-PLS) analysis. A diverse sample of 250 individuals engaged in agriculture, crafts, and tourism provides insights into the multifaceted nature of Bali's traditional job sectors. The measurement model assessment confirms the reliability and validity of latent variables, including technological adoption, changes in employment patterns, income levels, and community adaptation efforts. The structural model analysis reveals a positive influence of technological adoption on changes in employment patterns and income levels, indicating transformative opportunities within traditional occupations. However, challenges arise in maintaining income equity amidst shifts in employment patterns. The study also highlights the proactive response of communities, with technological adoption positively correlating with effective adaptation efforts. The model fit and sensitivity analysis affirm the robustness of the findings. This research contributes nuanced insights for policymakers and community leaders navigating the intersection of tradition and technological progress in Bali's evolving socio-economic landscape.